A geometria e os registros de representação semiótica em matemática - Baerle, Lucilene Dal Medico (2021)
This paper aims to verify how the Semiotic Representations Records Theory took part in the evolution of the ideas in geometry. In order to do so, some historical moments that played a role in building up this field in mathematics are highlighted and important theorists from these periods are presented. This way, one can observe the appearance and the revolution of signs (symbols) in mathematics, which culminates with the Semiotic Representation Records. With the aim of doing that, a review in the literature of mathematics was made and conceptions of sign from different areas were analysed, demonstrating the contributions from Charles Sanders Peirce, Ferdinand de Saussure and Gottlob Frege. Further on, conceptions from Raymond Duval and his Semiotic Representation Records Theory were examined taking into account its relevance to the area of Mathematical Education. It was possible to realize the revolution of signs prompted great advances for both the areas of mathematics and physics and also other related areas, besides technological advances that took place after this period.